THE EFFECT OF QUALITY COST MANAGEMENT ON FIRMS PROFITABILITY - Kereotu James, Oyadonghan; Luke, Ramond (British Journal of Marketing Studies, 2014)
The paramount objective of a firm or organization is to earn and maximize profit in the long run. To achieve this, firms put in place diverse strategies, one of which is quality improvement. This value-added activity has some attendant cost implications, so also do the failures in a firm’s product or service. These cost implications together make up the group of quality costs, and they put a strain on the profit making ability of a firm. The objectives of this study were to find out how quality costs can be managed and how their management affects the profitability of firms. The survey design was adopted to gather data from the hospitality industry in Bayelsa State. The correlation analysis (SPSS version 20) was used to analyze the data and from the results obtained it was concluded that there is a significant relationship between quality cost management and firm profitability. It was recommended that effective quality cost management systems be put in place by firms to enhance their profitability and that firms should channel more efforts towards prevention and appraisal activities, this will reduce the extent to which they spend on internal and external failures and lead to increased profitability